2018
DOI: 10.1186/s13293-018-0183-9
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-induced cardiotoxicity is suppressed by estrous-staged treatment and exogenous 17β-estradiol in female tumor-bearing spontaneously hypertensive rats

Abstract: BackgroundDoxorubicin (DOX), an anthracycline therapeutic, is widely used to treat a variety of cancer types and known to induce cardiomyopathy in a time and dose-dependent manner. Postmenopausal and hypertensive females are two high-risk groups for developing adverse effects following DOX treatment. This may suggest that endogenous reproductive hormones can in part suppress DOX-induced cardiotoxicity. Here, we investigated if the endogenous fluctuations in 17β-estradiol (E2) and progesterone (P4) can in part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
3
12
0
Order By: Relevance
“…Although intriguing, this hypothesis needs to be confirmed in future studies by administering testosterone to DOX-treated male mice. In female mice, we also demonstrate that acute DOX administration caused a significant reduction in uterus widths, indicating DOX-induced ovarian suppression as previously reported [37, 38]. Interestingly, ovariectomy of female mice did not alter the expression of renal sEH protein expression.…”
Section: Discussionsupporting
confidence: 89%
“…Although intriguing, this hypothesis needs to be confirmed in future studies by administering testosterone to DOX-treated male mice. In female mice, we also demonstrate that acute DOX administration caused a significant reduction in uterus widths, indicating DOX-induced ovarian suppression as previously reported [37, 38]. Interestingly, ovariectomy of female mice did not alter the expression of renal sEH protein expression.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, a recent study has shown that exogenous 17-β-estradiol administration suppressed DOX-induced cardiotoxicity in ovariectomized female tumor-bearing SHR rats. Surprisingly, co-administration of progesterone negated the protective effect of 17-β-estradiol [ 75 ]. In contrast to these findings, Gonzalez et al showed that ovariectomy did not exacerbate acute DOX-induced cardiotoxicity in tumor-bearing SHRs [ 64 ].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…We also explored the in uence of the features of animal model on cardiac function of DOX-treated trained animals, i.e., species, sex, cumulative dose of DOX and timing of nal cardiac function assessment. Although the role of estrogen on gender-related cardioprotection [48], including in the context of DOX-induced cardiomyopathy, is well documented [49], FS was similar between male and female animals. None of the studies using female animals [17-19, 23, 24, 27, 28] discussed the choice of this gender, took into consideration the in uence of female hormones in the outcomes of interest or reported particular methodological/monitoring aspects, such as handling estrous cycle.…”
Section: Discussionmentioning
confidence: 94%